A non-opioid analgesic implant for sustained post-operative intraperitoneal delivery of lidocaine, characterized using an ovine model. (December 2020) - Svirskis, Darren; Procter, Georgina; Sharma, Manisha; Bhusal, Prabhat; Dravid, Anusha; MacFater, Wiremu; Barazanchi, Ahmed; Bennet, Laura; Chandramouli, Kaushik; Sreebhavan, Sree; Agarwal, Priyanka; Amirapu, Satya; et al.
Abstract: Appropriate management of post-operative pain is an ongoing challenge in surgical practice. At present, systemic opioid administration is routinely used for analgesia in the post-operative setting. However, due to significant adverse effects and potential for misuse, there is a perceived need for the development of alternative, opioid-sparing treatment modalities. Continuous infusion of local anesthetic into the peritoneum after major abdominal surgery reduces pain and opioid consumption, and enhances recovery from surgery. Here we describe a non-opioid, poly(ethylene-co-vinyl-acetate) intraperitoneal implant for the sustained delivery of local anesthetic following major abdominal surgery. A radio-opaque core had the required mechanical strength to facilitate placement and removal procedures. This core was enclosed by an outer shell containing an evenly dispersed local anesthetic, lidocaine. Sustained release of lidocaine was observed in an ovine model over days and the movement modelled between peritoneal fluid and circulating plasma. While desirably high levels of lidocaine were achieved in the peritoneal space these were several orders of magnitude higher than blood levels, which remained well below toxic levels. A pharmacokinetic model is presented that incorporates in vitro release data to describe lidocaine concentrations in both peritoneal and plasma compartments, predicting similar release to that suggested by lidocaine concentrations remaining in the device after 3 and 7 days in situ . Histological analysis revealed similar inflammatory responses following implantation of the co-extruded implant and a commercially used silicone drain after three days. This non-opioid analgesic implant provides sustained release of lidocaine in an ovine model and is suitable for moving onto first in human trials. Graphical abstract: Image 1